Application of dried sewage sludge as phenol biosorbent - Thawornchaisit, Usarat; Pakulanon, Kesinee (My University, 2007)
The aim of this work was to determine the potential application of dried sewage sludge as a biosorbent for removing phenol from aqueous solution. Results showed that biosorption capacity was strongly influenced by the pH of the aqueous solution with an observed maximum phenol removal at pH around 6-8. Biosorption capacity increased when initial phenol concentration was increased to 110 mg/L but beyond this concentration, biosorption capacity decreased suggesting an inhibitory effect of phenol on biomass activity. Biosorption capacity decreased from 94 to 5 mg/g when biosorbent concentration was increased from 0.5 to 10 g/L suggesting a possible competitive effect of leachable heavy metals from the sludge. The effect of Cu2+ on biosorption capacity was also observed and the results confirmed that the phenol biosorption capacity decreased when concentration of Cu2+ in the sorption medium was increased up to 15 mg/L. Desorption of phenol using distilled deionized water was less than 2% suggesting a strong biosorption by the biomass. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Biosolids; Dried sewage sludge; Metals; Sorption